2020
DOI: 10.5489/cuaj.6221
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic prescribing habits and patterns of Canadian chief urology residents: A national survey

Abstract: Introduction: Prior studies have identified significant knowledge gaps in acute and chronic pain management among graduating urology residents as of five years ago. Since then, there has been increasing awareness of the impact of excessive opioid prescribing on long-term narcotic use and development of adverse narcotic-related events. However, it is unclear whether the attitudes and experience of graduating urology residents have changed. We set out to evaluate the attitudes and experience of graduating urolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The reported prevalence was 11% among patients with cancer surveyed in an emergency department (Silvestre et al, 2017) and 40% among patients with acute and chronic non-cancer pain (Buffington et al, 2019). Similarly, a survey of urology residents found that only 34% had ever counselled their patients about how to dispose of their excess opioids (Dergham et al, 2020). Patients likely received more clinician education in our study because of the increased attention to opioid-related harms generated by the public health crisis (Know More: Opioid Public Awareness, 2020;Opioid Stewardship, n.d.).…”
Section: Clinician Education About Opioid Disposalmentioning
confidence: 99%
“…The reported prevalence was 11% among patients with cancer surveyed in an emergency department (Silvestre et al, 2017) and 40% among patients with acute and chronic non-cancer pain (Buffington et al, 2019). Similarly, a survey of urology residents found that only 34% had ever counselled their patients about how to dispose of their excess opioids (Dergham et al, 2020). Patients likely received more clinician education in our study because of the increased attention to opioid-related harms generated by the public health crisis (Know More: Opioid Public Awareness, 2020;Opioid Stewardship, n.d.).…”
Section: Clinician Education About Opioid Disposalmentioning
confidence: 99%
“…With an ongoing opioid epidemic, surveys have looked at the narcotics prescribing habits of graduating residents. 3 When new technology was introduced into practice, such as prostate magnetic resonance imaging, QUEST assessed the experience of trainees into its interpretation. It has also gauged graduates' comfort with performing major oncological procedures independently and their level of exposure to robotic surgery when this surgical approach proliferated in Canadian academic institutions.…”
Section: Touma Et Almentioning
confidence: 99%